Encyclopedia of Life Sciences 2011
DOI: 10.1002/9780470015902.a0000378.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Spores

Abstract: Many heterotrophic eukaryotic organisms belong to the monophyletic kingdom Fungi. Because of their stationary life style, fungi reproduce by forming spores, cells that are specialised for dispersal to new locations by air, water or animals. Flagellated zoospores are produced by simple aquatic fungi. Most fungi are terrestrial, growing as hyphae and producing thick‐walled nonmotile spores. Asexual spores include sporangiospores and conidia, whereas sexual spores include zygospores, ascospores and basidiospores.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Increased labile carbon inputs can trigger the activation of dormant microorganisms by alleviation of their carbon limitation (Blagodatskaya and Kuzyakov, 2013). Thus, the increase in fungal diversity in PF soils might be the result of reactivated dormant fungal spores in response to ARE and elevated soil temperature (Moore‐Landecker, 2011; Lulakova et al ., 2019) and/or of an increase in opportunistic fungal taxa with enhanced resource utilization in response to ARE. Metatranscriptomic profiling also revealed that fungal activities quickly increased after permafrost thaw (Coolen and Orsi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Increased labile carbon inputs can trigger the activation of dormant microorganisms by alleviation of their carbon limitation (Blagodatskaya and Kuzyakov, 2013). Thus, the increase in fungal diversity in PF soils might be the result of reactivated dormant fungal spores in response to ARE and elevated soil temperature (Moore‐Landecker, 2011; Lulakova et al ., 2019) and/or of an increase in opportunistic fungal taxa with enhanced resource utilization in response to ARE. Metatranscriptomic profiling also revealed that fungal activities quickly increased after permafrost thaw (Coolen and Orsi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…, 2003 ). Without excluding a negative influence of PICF7 on the metabolic activity of VDAT‐36I hyphae, we rather related the absence/presence of hyphae vacuoles to different metabolic stages of the pathogen or to hyphal aging ( Moore‐Landecker, 1996 ), regardless the presence or not of the BCA.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal spores are found ubiquitously within the environment and are key to the dispersal and survival of many fungal species ( 1 , 2 ). Spores can endure severe temperatures, desiccation, and high levels of radiation and radical exposure, conditions fatal to many other life-forms ( 3 ).…”
Section: Introductionmentioning
confidence: 99%